2014
DOI: 10.15195/v1.a7
|View full text |Cite
|
Sign up to set email alerts
|

So You Think You Can Dance? Lessons from the US Private Equity Bubble

Abstract: This article develops a sociologically informed approach to market bubbles by integrating insights from financial-economic theory with the concepts of voice and dissimulation from other cases of distorted valuation studied by sociologists (e.g., witch hunts, unpopular norms, and support for authoritarian regimes). It draws on unique datalongitudinal interviews with private equity market participants during and after that market's mid-2000s bubble-to test key implications of two existing theories of bubbles and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Yet markets are also bound by connections, mutual dependencies, and reciprocal obligations-materialized through settlement systems, contractual linkages, and connectivity standards, but also through associations, professions, employment matching patterns, and others. (As Turco and Zuckerman (2014) show, exit is indeed quite limited, even in the putatively rational and calculative spheres of private equity.) Second, if relations emerge in connection to infrastructures, then the politics of relations cannot be contained within the categoremes of social actors and their mobilization.…”
Section: Some Final Thoughtsmentioning
confidence: 97%
“…Yet markets are also bound by connections, mutual dependencies, and reciprocal obligations-materialized through settlement systems, contractual linkages, and connectivity standards, but also through associations, professions, employment matching patterns, and others. (As Turco and Zuckerman (2014) show, exit is indeed quite limited, even in the putatively rational and calculative spheres of private equity.) Second, if relations emerge in connection to infrastructures, then the politics of relations cannot be contained within the categoremes of social actors and their mobilization.…”
Section: Some Final Thoughtsmentioning
confidence: 97%
“…Classic studies in behavioural finance and economic sociology have suggested that the likelihood for this to occur critically depends on the degrees of uncertainty (cf. Knight 1921, Keynes 1935, Tversky and Kahneman 1975, Nelson and Katzenstein 2014, Beckert 2016 and self-referentiality (Callon 1998, Temin and Voth 2004, MacKenzie 2006, Turco and Zuckerman 2014also Eichengreen et al 1996, Obstfeld 1996 that structure the environments under which investors decide. If information about economic fundamentals is readily available and if investors have the time and resources to process that information, they have incentives to analyze it carefully in order to transform 'unknown unknowns' into 'known unknowns' (cf.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Yet, as the connection between financial returns and the developments in underlying trends becomes weaker, the strength of these inhibitions wanes. In strongly self-referential environments, in which financial wins or losses are primarily determined by second-order obsevations, the logic can even turn the other way: in situations in which, as Keynes famously put it in his 'beauty contest' analogy, financial returns are not primarily a function of the actual unfolding of fundamental trends but of 'what average opinion expects the average opinion to be' (Keynes 1935, p. 156), anticipating upcoming investment fashionsin the hopes that one can 'jump off' before the bubble burstscan turn mimetic investment behaviour into an altogether rational strategy (Soros 1987, Temin and Voth 2004, Turco and Zuckerman 2014.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the absence of such measures may exacerbate mispricings, leading to bubbles (e.g., Turco and Zuckerman 2014). However, a necessary condition for successful short selling is the presence of a critical mass of investors who believe the stock to be overpriced.…”
Section: Hypothesis 1: Knowledge Sharing Is More Likely As the Amountmentioning
confidence: 99%